APPROPRIATENESS OF BURNING RATE MEASURING TECHNIQUE WITH THE MEASURING CONDITIONS AND REQUESTED DATA - Maraden, Ahmed Mohamed Ali; Stojan, Petr; Matyáš, Robert; Vodochodský, Ondřej (My University, 2018)
Burning rate data are usually obtained in several ways. Small-scale ballistic evaluation motors, constant volume vessels, standard strand burners, and full-scale motors with good instrumentation are the most common methods used to measure the ballistic properties of solid propellants. The objective of this work is to describe the facilities developed by each measuring technique and validate the newly developed SV-2 for strand burning measurements at low and high pressures. Modifications were made to use the SV-2 closed bomb as a Crawford bomb. The sample holder and the closing tip were totally changed to enable burn rate measurements at the beginning of strand burn measuring. The burning rate of different commercial extruded double bases was measured using the modified SV-2 strand burning and compared with the burning rate resulting from subscale rocket motors. The results showed that the burning rates generated from both methods are comparable and close to each other. One firing from the subscale motor or strand burning is equal to one point on the P-u, curve. The effect of the initial grain temperature on the combustion process was investigated using the SV-2 closed vessel method compared to the subscale rocket motor method. Changes in the ignition process were reported through the variations in the durations for different ignition zones. The burning criteria were studied through the P-t curves and the actual burning time. The burning parameters (pressure exponent n and temperature coefficient a) were calculated. The results showed that raising the initial grain temperature increases the ignitability, burning rate, and operating pressure. The suitability of the burning rate measuring technique is discussed. The subscale rocket motor method can be considered the method that most closely simulates reality despite the fact that it requires more money and effort and is time consuming. Strand burning measurements are favorable when measuring the burning rates at lower operating pressures (2-10 MPa), while the method is not suitable for investigating the initial grain temperature effect on the combustion process. The SV-2 closed vessel can be considered a more convenient method for measuring the burning rate from an economical point of view.
Vhodnost výběru měřící techniky ke stanovení rychlosti hoření dle podmínek měření
Keywords: burning rate; strand burning; subscale rocket motor; SV-2 closed vessel; double-base propellant; rychlost hoření; Crawfordova bomba; raketový motor; Stojanova bomba SV-2; homogenní tuhá pohonná hmota